A new mineral policy development framework for Pakistan. Issue 2 (3rd June 2019) - Ashraf, Hamid; Cawood, Frederick
Abstract : Purpose: The purpose of this paper is to develop a mineral policy development framework for Pakistan based on seven key elements derived from the gap analysis of Pakistan's current framework with leading developing minerals-based economies. Pakistan is gifted with significant mineral resources that have the potential to lift its economy and bring prosperity to its citizens. For this to happen, Pakistan must formulate a mineral policy based on leading practices to attract mining investment for economic growth. Design/methodology/approach: This paper develops a new mineral policy framework from the lessons derived from the gap analysis conducted in the first paper of this research. These lessons are called the "elements of development" which, after evaluation with the existing framework, will provide the suggested strategic fit measures for the formulation of the new mineral policy framework for Pakistan. Findings: A new mineral policy framework is proposed based on seven key enablers, namely, institutional framework, stable political economy, legal framework, regulatory framework, fiscal framework, stakeholder participation and sustainable development. A new organisational structure of the Ministry is also proposed based on the generally accepted organisational structure of tiers, implementation and regulatory bodies. Practical implications: The key constraints for Pakistan's mineral sector are as follows: the sector is lacking an enabling institutional framework for efficient access to mineral resources and lacks an enabling fiscal and regulatory framework including secure mineral rights system for mining to enhance the economic attractiveness of the sector. Originality/value: This paper presents original work on the development of a new mineral policy framework for Pakistan to extract maximum benefit from its mineral resources.